PERAN SKEPTISISME PROFESIONAL, TEKNOLOGI INFORMASI DAN ETIKA DALAM MENINGKATKAN KINERJA AUDITOR - Ingka Ingka; Asrini Asrini; Usman Rahman (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of professional skepticism, information technology, and auditor ethics on auditor performance at the Sidenreng Rappang Regency Inspectorate. Auditor performance is an important element in supporting accountability and transparency in regional financial management, especially in the public sector, which is prone to irregularities and fraud. Auditors are required to work professionally, objectively, and ethically to ensure that financial reports are presented reliably and in accordance with applicable principles. This study used a quantitative approach with a questionnaire distributed to 36 auditors as respondents. The data analysis technique used was multiple linear regression. The results of the study indicated that, partially, professional skepticism had a positive and significant effect on auditor performance, information technology had a positive and significant effect on auditor performance, and auditor ethics had a positive and significant effect on auditor performance. Simultaneously, all three variables also significantly influence overall auditor performance.of technology, and enforcement of ethics in improving the quality of public sector audits.